Multiple hydatid cysts in rare locations treated with albendazole: A case report - Somayeh Sadeghi; Farzin Ghiasi; Amir Aria; Mahnaz Momenzadeh; Elahe Nasri; Shadi Reisizadeh Mobarakeh (Advanced Biomedical Research, 2023)
Hydatid cyst is a common disease between humans and animals. Foods that are contaminated with eggs of echinococcal species are the cause of hydatid disease. Although this parasite affects different organs, the liver and lungs are very susceptible but the cardiac hydatid disease is very rare. We report the case of a 33-year-old man admitted because of chest pain. Echocardiography had shown suspected round cyst in the myocardium. More diagnostic managements had demonstrated cystic lesion in the liver, spleen and lungs. There were also multiple cystic lesions in both lungs. He refused surgery and was taken to medical therapy. Myocardial involvement by hydatid cysts occurs very rarely. The main treatment approach for cardiac hydatid disease in patients should be surgery. The alternative treatment was done to those who refused surgical removal, adjuvant therapy such as albendazole for at least 1–6 months. Because myocardial involvement by hydatid cysts is uncommon, we decided to report this rare case.